Enhancing Students’ Speaking Ability through Community Learning Method - Zakaria, Aris; Anjariyanto, Anjariyanto; Mitsalina, Endah (Scripta : English Department Journal, 2023)
This Classroom Action Research is motivated by the low learning ability of students and the lack of interest in learning English at SMK Ma’arif 1 Kebumen. Therefore, researchers conducted this study. Research conducted at SMK Ma’arif 1 Kebumen aims to find out and describe how the Community Learning Method can improve students’ speaking skills. Data from both quantitative and qualitative sources were used in the research. This research was conducted at SMK Ma’arif 1 Kebumen involving teachers and class XII students. Classroom action research is the sort of study, and it has two cycles. Planning, implementing, observing, and reflecting make up each cycle. From the first condition to the last condition there was an increase in student learning from students who were more active, dared to speak English and the average pretest score was 77.60 and the posttest score was 81.25. In addition to collecting data through pre-test and post-test, researchers also conducted interviews with teachers and students during the learning process. From the results of interview tests conducted in cycle one the teacher and students explained that students were still nervous and embarrassed to speak English. In the second cycle there has been a lot of improvement with the results of the interview test concluding that students are starting to actively speak English, have confidence and the process of learning English has increased. In this study the researchers succeeded in improving students’ speaking skills by using this method.